Citoyenneté et éducation par la société - Labarre, Guy (Pratiques & techniques, 2019)
Exploring the role played by the society in the relationship between citizenship and education is at the heart of the issues addressed in this book, which was the result of a collective reflection held on 8-9 November 2016 during a symposium organized in Besançon. Gathering historians, philosophers and sociologists, three reflection axis are developed: the first focuses on the discourses produced by society itself on citizenship; the second deals with the diffusion of the notion of citizenship in society; the third focuses on the crises of citizenship and their responses.